Geofenced marketing to Spanish-language sports media consumers in Kansas - Cordero, Javier A. (My University, 2026)
When it comes to sports in Kansas, many sports fans prefer consuming sports broadcasts in languages other than English. Specifically, there is a large audience for Spanish-language broadcasting. Not providing Spanish-language broadcasts for sports turns away consumers who do not speak English natively. Having this type of sports content in Spanish-language will allow a large group of primary Spanish speakers feeling excluded due to the media not being in their native language. Making these sports broadcasts more readily available to these groups will allow more people to listen as it will eliminate the search factor. Findings from the literature suggest that Hispanic and Latinos all over Kansas would consume more sports broadcasts if they were available in their native language. Many of these Hispanic and Latino listeners suggested that when they listen to a sports broadcast in English, they often cannot keep up with the language and lose information and crucial context due to the language barrier. This loss of information makes understanding an unfamiliar game, such as American football that much more complex for non-English speakers. The overall findings from this study show that Hispanic and Latino audiences want to consume different types of sports media, when it is in their native language. Hispanic and Latino communities across Kansas have considerable potential when it comes to increasing brand awareness and revenue. These communities currently are underserved when it comes to Spanish-language sports media. Providing this type of media to the Hispanic or Latino communities can bridge cultural gaps while growing and diversifying sports fans.
Keywords: Spanish-language sports broadcasting; Hispanic and Latino audience engagement; Sports media consumption behavior; Multicultural marketing in sports; Media dependency theory; Sports sponsorship and brand strategy